A study on awareness about HIV among female sex workers of Davangere, Karnataka, India: a cross-sectional study - H. O., Girish; Haladi, Sudhir Prabhu; P. S., Balu (International Journal Of Community Medicine And Public Health, 2016)
Background: HIV/AIDS is a major medical, public health as well as a grave socioeconomic challenge to the world. In India, sexual transmission is responsible for 87 percent of reported HIV cases. Female sex workers form a separate and largest group among the core high risk groups. The main objectives were to know the level of awareness about HIV among female sex workers of Davangere city, Karnataka, India. Methods: A Cross-sectional community based descriptive study conducted at Davanagere city involving 200 female sex workers using modified questionnaire of behaviour surveillance survey. Results: The mean age was 32.7 years. 64% were illiterates, 56.5% were married and living with their spouse. Good proportion of participants had awareness about the mode of spread & prevention of HIV, but the awareness needs to be improved in some components. Conclusions: The proportion of awareness would be because of the exposure of female sex workers to the targeted intervention programme which helps them in understanding about the disease.